Palliavite tratment of extrahepatic malign obstruction with plastic and metalic stents: a comparsion - M. Hadi YAŞA,; C. YURDAYDIN,; K. BAHAR,; S. KARAYALÇIN,; A.R. BEYLER,; H. ÖZKAN,; N. ÖRMECİ,; A. DÖKMECİ, (Turkish Journal of Gastroenterology, 2019)
-